2018
DOI: 10.1002/cphc.201800955
|View full text |Cite
|
Sign up to set email alerts
|

“Through‐Space” Relativistic Effects on NMR Chemical Shifts of Pyridinium Halide Ionic Liquids

Abstract: We have investigated, using two‐component relativistic density functional theory (DFT) at ZORA‐SO‐BP86 and ZORA‐SO‐PBE0 level, the occurrence of relativistic effects on the 1H, 13C, and 15N NMR chemical shifts of 1‐methylpyridinium halides [MP][X] and 1‐butyl‐3‐methylpyridinium trihalides [BMP][X3] ionic liquids (ILs) (X=Cl, Br, I) as a result of a non‐covalent interaction with the heavy anions. Our results indicate a sizeable deshielding effect in ion pairs when the anion is I− and I3−. A smaller, though nonz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 119 publications
1
2
0
Order By: Relevance
“…It seems likely that the increasing downfield shift is mainly due to the so-called Inverse Halogen Dependence (IHD) which is caused by spin orbit coupling on the heavy halogen atom and its effect on the 1 H NMR shift. Similar effects for through space interactions and an IHD have been reported for iodo alkyl and aryl compounds by Kaupp et al and for ion pairs by Ariai et al 52,53 The 13 C{ 1 H} NMR spectra of the di-and monoarylbismuth(III) halides also exhibit a downfield shift for the C-6 carbon resonance signals, which follows the order Fig. S12, ESI †).…”
Section: Computational Study Of Diarylbismuth Halides 2-4 and The Diasupporting
confidence: 77%
“…It seems likely that the increasing downfield shift is mainly due to the so-called Inverse Halogen Dependence (IHD) which is caused by spin orbit coupling on the heavy halogen atom and its effect on the 1 H NMR shift. Similar effects for through space interactions and an IHD have been reported for iodo alkyl and aryl compounds by Kaupp et al and for ion pairs by Ariai et al 52,53 The 13 C{ 1 H} NMR spectra of the di-and monoarylbismuth(III) halides also exhibit a downfield shift for the C-6 carbon resonance signals, which follows the order Fig. S12, ESI †).…”
Section: Computational Study Of Diarylbismuth Halides 2-4 and The Diasupporting
confidence: 77%
“…The possibility of “through-space” propagation of SO-HALA effects in pyridinium halide ionic liquids has been investigated computationally . Using various computational models, δ SO ( 13 C) up to +3 ppm was predicted at the pyridinium carbon atoms when pyridinium was involved in an ion pair with I 3 – , but this effect vanished with the Cl 3 – analog.…”
Section: Trends In So-hala Shifts Across the Periodic Tablementioning
confidence: 99%
“…The possibility of "through-space" propagation of SO-HALA effects in pyridinium halide ionic liquids has been investigated computationally. 211 Using various computational models, δ SO ( 13 C) up to +3 ppm was predicted at the pyridinium carbon atoms when pyridinium was involved in an ion pair with I 3 − , but this effect vanished with the Cl 3 − analog. The authors concluded that it may be challenging to find experimental evidence to support these computational predictions, owing to the short lifetime of the investigated ion pairs in a liquid environment.…”
Section: See Sections 2 and 3)mentioning
confidence: 99%